3D-printed origami electronics using percolative conductors. Issue 40 (20th June 2018) - Jo, Yejin; Jeong, Du Won; Lee, Jeong-O; Choi, Youngmin; Jeong, Sunho
Abstract : Recently, three-dimensional (3D) printing has garnered tremendous amounts of attention in various applications. Abstract : Recently, three-dimensional (3D) printing has garnered tremendous amounts of attention in various applications. In this study, we suggest a facile means of creating 3D-printed foldable electrodes on paper via the direct printing of composite pastes consisting of conductive fillers and a thermoplastic elastomer. The 3D-printability of the prepared composite pastes is investigated depending on the rheological properties. It is revealed that the composite paste with a high storage modulus would enable the formation of highly conductive features with a resistance of 0.4 Ω cm −1 on three-dimensional paper structures. The mechanical bending/folding stability levels of the printed electrodes are evaluated to judge the possibility of realizing 3D-printed origami electronics. The resistance is changed slightly with a normalized resistance value of 2.3, when the printed electrodes are folded with a folding angle of 150°. It is demonstrated that the 3D-printed composite electrodes are applicable to various origami electronics, including electrical circuits, strain sensors and electrochemical sensors.